(untitled) (Research, Society and Development, 2021)
Cardiovascular diseases (CVD) are one of the main public health problems of today. Where, according to data from the World Health Organization (2017), about 27% of mortality records in the world were due to CVD, while in Brazil, they accounted for 31% of deaths in the general population. Despite advances in obstetrics and advances in early detection methods, neonates resulting from premature births are twice as likely to present cardiac abnormalities. Therefore, the present study aims to analyze the factors for the onset of CVD in premature babies, identifying the main causes for the occurrence of heart diseases in them, which heart diseases are more frequent to find, their clinical manifestations in order to perform the appropriate diagnosis and the procedures used in the treatment, presenting a vision focused on Biomedicine. To this end, a literature review of the narrative type was carried out through the databases of Google Scholar, Virtual Health Library (VHL), Pub Med, Scientific Electronic Library OnLine (SciELO). The studies found presented factors that can relate the presentation of heart diseases in premature babies, such as gestational age, genetic factors, maternal lifestyle, among others. However, despite the results found there are still few files on the subject, making further studies necessary, as it is a very relevant topic and can contribute significantly to the area of public health.